120-36 = 84
84 = 2*2*3*7
See what you can do with that.
Tasha believes that she can rewrite the difference 120 - 36 as a product of the two numbers and another difference. Is she correct?
4 answers
(120)(-36)(x) = 120-36
-(36)(120)x = 84
x = -84/(36*120) = -7/360
so all we have to do is write -7/360 as the difference
e.g. -7/360 = 353/360 - 1
so 120 - 36 = (120)(-36)(353/360 - 1)
which is the product of the two numbers and another difference
-(36)(120)x = 84
x = -84/(36*120) = -7/360
so all we have to do is write -7/360 as the difference
e.g. -7/360 = 353/360 - 1
so 120 - 36 = (120)(-36)(353/360 - 1)
which is the product of the two numbers and another difference
Yes
I don't know what to do